Functional analysis of compound heterozygous variations in the CLCNKB gene in a patient with Bartter syndrome type Ⅲ - Yu-wen Cai; Xue-qin Cheng; Ruo-chen Che; Chun-li Wang; Song-ming Huang (Editorial Department of Journal of Clinical Nephrology, 2024)
ObjectiveTo explore the functional characteristics of a patient of Bartter syndrome type III and compound heterozygous mutations in CLCNKB gene and explore the rescue effect of cystic fibrosis transmembrane conductance regulator modulator compound VX-809 on CLCNKB gene missense variant.MethodsA retrospective analysis was conducted for a hospitalized patient of Bartter syndrome type III on September 2, 2019. Clinical characteristics, growth and development status, laboratory findings and genetic data were reviewed. Wild-type and variant CLCNKB genes were separately transfected into human embryonic kidney 293 cells (HEK293) and the expression levels of ClC-Kb protein in each group detected by Western blot. The differences in protein expression between wild-type and variant type were compared by unpaired t-test. Additionally, immunofluorescent stain was utilized for examining the subcellular localization of ClC-Kb protein. And cystic fibrosis transmembrane conductance regulator modulator compound VX-809 was employed for treating cells after transfecting with a over-expressing variant in CLCNKB gene.ResultsThis 32-month-old girl presented with hypokalemia, hypochloremia, metabolic alkalosis, renal salt wasting and normal blood pressure in all four extremities. Genetic testing results revealed compound heterozygous variations in CLCNKB gene. Transfection of two variant plasmids (p.F213C & p. Y466Mfs13) into HEK293 cells indicated that the expression of variant ClC-Kb protein was significantly lower than that of wild-type (P<0.01 for both). Frameshift variant resulted in a lower molecular weight band (~5.5×104). Immunofluorescent localization assays revealed that both variants were retained in cytoplasm. Treatment of HEK293 cells transfected with p. F213C variant with VX-809 resulted in a dose-dependent significant spike in membrane expression of ClC-Kb protein.ConclusionTwo variants of CLCNKB gene result in lower expression and abnormal localization of ClC-Kb protein. Compound VX-809 may partially correct the protein expression defects caused by CLCNKB gene variants in patients of Bartter syndrome type III. It hints at new therapeutic potentials for Bartter syndrome type III.